Source of Water and Potential Sanitizers and Biological Antimicrobials for Alternative Poultry Processing Food Safety Applications - Micciche, Andrew C.; Rubinelli, Peter M.; Ricke, Steven C. (Frontiers in Sustainable Food Systems, 2018)
The landscape of commercial poultry production is changing due to increasing trends in consumer preference for organic sources of poultry products. This is in part due to perceptions regarding food safety and environmental issues, along with concerns for livestock animal welfare. Consequently, alternative poultry production systems such as small-scale farming and mobile poultry processing units (MPPUs) have achieved a certain level of popularity. However, these alternative production systems, like conventional poultry processing systems, face food safety concerns, due to potential of Campylobacter and Salmonella prevalence. Unlike stationary processing systems, MPPUs may have limited access to sanitation products as they often attempt to comply with organic processing regulations. They may also have limited access to a consistent, high quality water supply which may pose additional food safety and microbial contamination concerns. Due to these food safety concerns and potential limitations on traditional sanitizers, botanicals, organic acids, dry acids, bacteriocins, and phages may offer alternative potential solutions to ensure poultry product safety. The objective of this review is to discuss food safety concerns within alternative poultry processing systems, particularly MPPUs, and describe potential sanitizer strategies.